India’s Export Performance and Its Determinants: An ARDL Bounds Testing Approach - Saikia, Karuna Kanta (Indian Journal of Finance, 2013)
The export-led growth strategy adopted in the aftermath of the economic crisis of 1991 has removed all sorts of bias against exports. In this context, this paper examined the export performance and its determinants during the period from 1981-2011. The export growth has been higher in the post reform period as compared to the pre - liberalization period. The higher trade GDP ratio indicates that the Indian economy is more deeply integrated with the world economy. However, declining export-import ratio reflecting a deteriorating trade balance has been a cause of concern for the country. An ARDL bound testing approach to cointegration was adopted to identify the determinants of export performance. The empirical results indicated a long run as well as short run relation between the exports and the GDP, income of foreign countries (FGDP), real and effective exchange rate (REER), trade liberalization index (TLI), and foreign direct investment (FDI). While the impact of RGDP, TLI, and REER were positive; the impact of FGDP and FDI were found to be negative. The policy implication of the negative effect of the FGDP is that the government should take initiatives to improve the quality of local products and should reduce the average cost of production to increase the share of Indian exports in the world market. To realize the advantage of FDI for export growth, the government should provide infrastructural facilities and remove all barriers to attract more export oriented FDI, as is the case with China and Singapore.